Para além do Rio Grande: Os impactos da economia paulista sobre O Triângulo Mineiro - Oliveira, Paulo Roberto de [UNESP] (FapUNIFESP (SciELO), 2008)
In this work our intention was to investigate the impact of Sao Paulo's coffee economy on the Minas Gerais Triangle Region, during its penetration into the area because of the extension of the Mogiana Railroad Company in 1889. We attempt to understand the impact caused along this coffee railroad in a region where this product almost did not exist, and the changes that occurred to the economic panorama of the region. Furthermore we have taken as an example, the city of Uberaba, the most important, in this region at that time.
Beyond the Rio Grande: The impact of Sao Paulo's coffee economy on the Minas Gerais Triangle Region
Keywords: Brazil's First Republic; Railroads; The Minas Gerais Triangle Region